Možnosti vzpostavitve duhovne oskrbe v armadi Republike Severne Makedonije - Brožič, Liliana (Edinost in dialog, 2025)
The article deals with spiritual care in the Army of the Republic of North Macedonia (ARSM) as a hitherto unregulated but important area of military organisation in terms of holistic care for members of the armed forces and human rights. Using historical, descriptive and analytical methods, as well as a deductive approach, the paper presents an analysis of the historical development, the legal framework and the attitudes of ARSM members towards spiritual care. Particular attention is paid to a comparative analysis of the arrangements in the Republic of Croatia and the Republic of Slovenia, where spiritual care is already in place on the basis of constitutional provisions and international agreements. The findings show that there is a legal and societal basis for the introduction of military spiritual care in the Republic of Macedonia, but that there is a lack of political will and institutional initiative.
Keywords: Armada Republike Severne Makedonije; Armed Forces of the Republic of Croatia; Army of the Republic of North Macedonia; duhovna oskrba; military; oborožene sile; Oborožene sile Republike Hrvaške; religion; Slovenian Armed Forces; Slovenska vojska; spiritual care; vera